2014
DOI: 10.7314/apjcp.2014.15.21.9107
|View full text |Cite
|
Sign up to set email alerts
|

PLCE1 rs2274223 Polymorphism and Susceptibility to Esophageal Cancer: a Meta-analysis

Abstract: Purpose: To investigate and study the relationship between the PLCE1 rs2274223 gene polymorphism and susceptibility to esophageal cancer by meta-analysis. Materials and Methods: The literature was searched in Wanfang, CNKI, PubMed, CBM, Web of Science, MEDLINE, EMBASE, Springer, Elsevier and Cochrane databases from the date of January 1 st 2004 to April 1 st 2014 to collect case-control studies on the PLCE1 polymorphism and susceptibility to esophageal cancer. For the population genotype distributions of both … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 20 publications
1
5
0
Order By: Relevance
“…The above findings were consistent with those reported by Umar (58), but slightly different from the findings of Xue et al (14), which suggested that rs2274223 polymorphism was not associated with susceptibility to gastric cancer. The results based on the esophageal cancer subgroup were consistent with the results of Wang et al (59) and Guo et al (60). Moreover, the results of the stratified analysis indicated that the rs2274223 polymorphism was associated with cancer susceptibility in Asians but not in Caucasians, consistent with the findings of Umar et al (58).…”
Section: Discussionsupporting
confidence: 91%
“…The above findings were consistent with those reported by Umar (58), but slightly different from the findings of Xue et al (14), which suggested that rs2274223 polymorphism was not associated with susceptibility to gastric cancer. The results based on the esophageal cancer subgroup were consistent with the results of Wang et al (59) and Guo et al (60). Moreover, the results of the stratified analysis indicated that the rs2274223 polymorphism was associated with cancer susceptibility in Asians but not in Caucasians, consistent with the findings of Umar et al (58).…”
Section: Discussionsupporting
confidence: 91%
“…For 51 SNPs identified by meta‐analysis, 38 SNPs had statistically significant association with EC or ESCC susceptibility . Meta‐analysis results showed that there were 27 SNPs associated with increased EC or ESCC risk, whereas 11 SNPs decreased the risk of EC or ESCC risk.…”
Section: Resultsmentioning
confidence: 94%
“…Gu, et al 14 found that PLCE1 rs2274223 could be used to predict the risk of esophageal cancer. Also, Guo, et al 15 revealed that PLCE1 rs2274223 polymorphism is associated with esophageal cancer. Study has also shown that PLCE1 regulates cell growth, proliferation, and differentiation and affects cytoskeleton change, cell movement, cell apoptosis, tumor growth and development, and other biological behaviors.…”
Section: Discussionmentioning
confidence: 99%